Application of the methods of monotonic sequences - Juozas Juvencijus Mačys (Lietuvos Matematikos Rinkinys)
The method of monotonic sequences (see [1], [2]) is considered and the issue of its exactness is discussed. It is shown how the method can be applied to finite sums with a large number of summands.